2015
DOI: 10.1111/tpj.13056
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Cucumber metal tolerance protein CsMTP9 is a plasma membrane H+‐coupled antiporter involved in the Mn2+ and Cd2+ efflux from root cells

Abstract: These authors contributed equally to this work. SUMMARYMembers of the plant metal tolerance protein (MTP) family have been classified into three major groupsZn-CDF, Mn-CDF and Zn/Fe-CDF -however, the selectivity of most of the MTPs has not been confirmed yet. Cucumber gene CsMTP9 encoding a putative CDF transporter homologous to members of the Mn-CDF cluster is expressed exclusively in roots. The relative abundance of CsMTP9 transcript and protein in roots is significantly increased under Mn excess and Cd. Imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 51 publications
1
50
1
2
Order By: Relevance
“…As plant MTP7 proteins have been classified as putative Fe/Zn transporters (Gustin et al ., ), we assumed that the CsMTP7 transcripts could be affected by changes in cellular Fe or Zn homeostasis. To test this hypothesis, we analyzed the levels of sCsMTP7 and lCsMTP7 transcripts in the roots of cucumbers grown under different Fe and Zn availability as well as under the excess of other heavy metals, such as Mn, Ni, Co or Cd, which also serve as substrates of plant MTP transporters (Persans et al ., ; Delhaize et al ., , ; Arrivault et al ., ; Peiter et al ., ; Yuan et al ., ; Menguer et al ., ; Migocka et al ., , ,b; Pedas et al ., ). As shown in Figure (b), the sCsMTP7 mRNA/ lCsMTP7 mRNA ratio was significantly altered depending on the external Fe level.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As plant MTP7 proteins have been classified as putative Fe/Zn transporters (Gustin et al ., ), we assumed that the CsMTP7 transcripts could be affected by changes in cellular Fe or Zn homeostasis. To test this hypothesis, we analyzed the levels of sCsMTP7 and lCsMTP7 transcripts in the roots of cucumbers grown under different Fe and Zn availability as well as under the excess of other heavy metals, such as Mn, Ni, Co or Cd, which also serve as substrates of plant MTP transporters (Persans et al ., ; Delhaize et al ., , ; Arrivault et al ., ; Peiter et al ., ; Yuan et al ., ; Menguer et al ., ; Migocka et al ., , ,b; Pedas et al ., ). As shown in Figure (b), the sCsMTP7 mRNA/ lCsMTP7 mRNA ratio was significantly altered depending on the external Fe level.…”
Section: Resultsmentioning
confidence: 99%
“…The CDF proteins so far characterized in plants localize to the tonoplast (MTP1, MTP3, MTP4 and MTP8) (Delhaize et al ., ; Desbrosses‐Fonrouge et al ., ; Arrivault et al ., ; Migocka et al ., , 2015a), the Golgi/prevacuolar system (MTP11, MTP8, MTP5 and MTP12) (Delhaize et al ., ; Peiter et al ., ; Pedas et al ., ) or the plasma membrane (MTP9) (Migocka et al ., 2015b; Ueno et al ., ) and contribute to the efflux of a wide range of heavy metals, including Zn, Cd and Mn, out of the cytoplasm. CsMTP7 localizes to the mitochondria of plant and yeast cells, consistent with the presence of the putative mitochondrial targeting sequence within the N‐terminal domain of the cucumber protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malondialdehyde (MDA), one of the decomposition products of lipid peroxidation, can modify active substrates in plant cells, including nucleic acids, proteins and saccharides11. To become resistant to Cd 2+ toxicity, plants have developed several strategies, such as inducing the alternative respiratory pathway11, activating antioxidants and glutathione (GSH)12, and regulating the influx and efflux of heavy metals1314, as well as regulating the levels of heavy metal chelators, phytochelatins (PCs)15 and metallothioneins (MTs)16.…”
mentioning
confidence: 99%
“…Migocka and his colleagues reported that the vacuolar membrane localized cucumber-MTP8, a Mn transporter, which helps maintain Mn homeostasis in root cells18. The same group also found that CsMTP9 is a plasma membrane H + -coupled Mn 2+ and Cd 2+ antiporter involved in the efflux of Mn and Cd from cucumber root cells by transporting both metals from the endodermis into vascular tissues36. Golgi localized Mn 2+ transport proteins, MTP8.1 and MTP8.2, are involved in barley intracellular Mn homeostasis37.…”
mentioning
confidence: 93%